Embodied spatial mobility (in)justice: Cycling refrains and pedalling geographies of men, masculinities, and love. Issue 4 (2nd July 2021) - Waitt, Gordon; Buchanan, Ian; Lea, Tess; Fuller, Glen
Abstract: This paper seeks to better understand spatial mobility justice with reference to the bodily sensations of cycling, discerned here as different pedalling rhythms in emergent territories that our participants narrate as "love." Differential or striated mobility is not just the result of gendered, classed, and racialised social norms but is productive of the frictions and affordances of these social hierarchies. We build on these arguments by asking the question: Are some places more affective than others in working for and against mobility justice for cyclists? This paper takes up this challenge by drawing on Deleuze and Guattari's notions of the refrain. In this way, mobility justice is conceptualised as repeated sequences of living that temporarily order space, time, bodies, and selves through which differential subjects and uneven spatial conditions are constituted. Through an appreciation of mobility justice as a mobile assemblage comprised of rhythmic qualities of spatiality, contingent subjects, embodied knowledge, and fleeting practice, the paper draws on the experiences of three men‐who‐cycle and drive to map processes of gendered, classed, sexed, and aged inclusion and exclusion from public space in the car‐dominated small city of Wollongong, Australia. Considering the politics of "love, " we explore the possibility of cyclists, pedestrians, and drivers to move together, or not, in proximity with each other. Abstract : This paper seeks to better understand spatial mobility justice with reference to the bodily sensations of cycling, discerned here as different pedalling rhythms in emergent territories that our participants narrate as "love." Differential or striated mobility is not just the result of gendered, classed, and racialised social norms but is productive of the frictions and affordances of these social hierarchies.